The sea of monsters - Riordan, Rick. (New York : Miramax Books/Hyperion Books for Children, 2006)
Demi-god Percy Jackson and his friends must journey into the Sea of Monsters to save their camp. But first Percy will discover a secret that makes him wonder whether being claimed as Poseidon's son is an honor or a cruel joke.
Keywords: Mythology, Greek; Mythology, Greek; Camps; Friendship; Fathers and sons; Poseidon (Greek deity)